Fermionic analysis of Davey-Stewartson dromions - Jaulent, M.; Manna, M. A. [UNESP]; Martinez-Alonso, L. (Elsevier, 1990)
Dromion solutions of the Davey-Stewartson equation are analysed from the point of view of the bilinear formalism. The corresponding τ-functions are expressed in terms of vacuum expectation values of Clifford operators and their group-theoretical content is provided. Explicit computation performed with the help of Wick's theorem allows us to characterize the dromion interaction. © 1990.